Design of calcium phosphate scaffolds with controlled simvastatin release by plasma polymerisation. (1st June 2016) - Canal, Cristina; Khurana, Kanupriya; Gallinetti, Sara; Bhatt, Sudhir; Pulpytel, Jérome; Arefi-Khonsari, Farzaneh; Ginebra, Maria-Pau
Abstract: Calcium Phosphates (CaPs) have excellent bone regeneration capacity, and their combination with specific drugs is of interest because it allows adding new functionalities. In CaPs, drug release is mainly driven by diffusion, which is strongly affected by the porosity of the matrix and the drug–material interaction. Therefore, it is very difficult to tune their drug release properties beyond their intrinsic properties. Furthermore, when the CaPs are designed as scaffolds, the increased complexity of the macrostructure further complicates the issue. This work investigates for the first time the use of biocompatible plasma-polymers to provide a tool to control drug release from drug-loaded CaP scaffolds with complex surfaces and intricate 3D structure. Two different CaPs were selected displaying great differences in microstructure: low-temperature CaPs (Calcium-deficient hydroxyapatite cements, CDHA) and sintered CaP ceramics (β-Tricalcium Phosphate, β-TCP). The deposition of PCL-co-PEG (1:4) copolymers on CaPs was achieved by a low pressure plasma process, which allowed coating the inner regions of the scaffolds up to a certain depth. The coating covered the micro and nanopores of the CaPs surface and produced complex geometries presenting a nano and micro rough morphology which lead to low wettability despite the hydrophilicity of the copolymer. Plasma coating with PCL-co-PEG on scaffolds loaded with Simvastatin acid (potentially osteogenic and angiogenic) allowed delaying and modulating the drug release from the bone scaffolds depending on the thickness of the layer deposited, which, in turn depends on the initial specific surface area of the CaP. Graphical abstract: Highlights: Tuning Calcium Phosphate (CaP) bone graft drug release is challenging. β-TCP and CDHA 3D scaffolds were coated with PCL-co-PEG biocompatible polymers. Hydrophobic complex surface geometries were obtained despite the copolymer hydrophilicity. Plasma coating on scaffolds loaded with Simvastatin acid delayed and tuned the release. Release profiles depended on the coating thickness, which rests upon the specific surface area of the CaP.